Development of cure kinetics models for drying nitrile-butadiene rubber latex film with computational fluid dynamics simulation - Chakrit Suvanjumrat; Kittipos Loksupapaiboon (International Journal of Thermofluids)
Dipped products undergo vulcanization or a curing process to create rubber film coats on their molds. A significant challenge in the rubber latex curing process is achieving an even degree of curing in dip-molded products. In the current era, simulation methods like Computational Fluid Dynamics (CFD) offer a solution to this issue. This study focuses on developing CFD techniques to simulate the curing process of nitrile-butadiene rubber (NBR) latex film. Non-isothermal differential scanning calorimetry tests were performed for NBR latex curing with constant heating rates of 2.5, 5, 10, and 20 K/min. Consequently, the activation energy was determined and utilized to derive curing reaction models. Fourteen reaction models were implemented to identify the most suitable one, which was determined to exhibit R² values ranging from 0.991 to 0.998 when compared with experimental data. The proposed curing reaction model was subsequently developed and integrated into the CHT solver of the OpenFOAM software. The modified OpenFOAM solver was validated with experimental results of hot-air flow past a squared NBR film, confirming its accuracy. It was applied using conjugate heat transfer and convective boundary condition techniques for curing NBR film, achieving an R² of 0.9749 and 0.9748, respectively. These applications enabled the visualization of the NBR curing degree distribution on the surface of thin film. The proposed solver serves as a valuable tool for estimating optimal conditions in the curing process of rubber-coated films on complicated shapes of dipped products, such as rubber gloves, facilitating further research.